Relationship between hygroscopicity reduction and morphology evolution of Y2Mo3O12 doped with (LiMg)3+. (May 2015) - Cheng, Y.G.; Liu, X.S.; Song, W.B.; Yuan, B.H.; Wang, X.L.; Chao, M.J.; Liang, E.J.
Graphical abstract: Highlights: Hygroscopicity of Y2 Mo3 O12 is reduced due to substitution of (LiMg) 3+ for Y 3+ . Morphology evolution of Y2 Mo3 O12 crystal is investigated by introducing (LiMg) 3+ . Thermal expansion versus water releasing of Y2 Mo3 O12 is suppressed greatly. Coefficient of thermal expansion of (LiMg)2 Mo3 O12 is reduced by introducing Y 3+ . Abstract: The morphology evolution and hygroscopicity reduction of Y2 Mo3 O12 crystal are investigated by introducing (LiMg) 3+ . With increasing the content of (LiMg) 3+, the hygroscopicity of Y2 Mo3 O12 is reduced obviously depending on the XRD, Raman and DSC/TG results, and the morphology of Y2 Mo3 O12 transforms remarkably from amorphous crystal to octahedra and then rod. The results suggest the effects of (LiMg) 3+ on repelling water molecules and improving the growth of Y2 Mo3 O12 crystal, which could be a reflection of the decrease of micro-channels in the structure. Some (LiMg) 3+ substitute Y 3+ in Y2 Mo3 O12 to form solid solutions of (LiMg)2− x Y x Mo3 O12 with octahedra and then rod, and excess (LiMg) 3+ leads to the formation of (LiMg)2 Mo3 O12 due to the difficulty in substituting Y 3+ with (LiMg) 3+ . The substitution of Y 3+ for (LiMg) 3+ reduces the thermal expansion coefficient of Li-ion battery material of (LiMg)2 Mo3 O12 .